MICROWAVE-ASSISTED EXTRACTION OF PECTIN FROM BABY JAVA ORANGE (Citrus sinensis) PEEL AND ITS CHARACTERISATION - Susinggih Wijana; Nur Lailatul Rahmah; Siti Insyirah Fadhilah (Jurnal Teknologi Pertanian, 2023)
Baby java orange (Citrus sinensis) is the main ingredient for various products. Pectin as a baby java orange peel substance is extracted using various methods. Microwave-assisted extraction is a method that uses heat energy dissipated by the volume setting from the transmitting medium. The objective of the study was to evaluate the effect of orange peel powder: acid solution ratio (1:10, 1:15, 1:20 b/v)  and extraction time (5, 10, 20 min) on characteristics of extracted pectin by using MAE (Microwave-Assisted Extraction) at 2.450 MHz. The best result was a 15-minute extraction time and 1:15 as the material: acid solution ratio. The treatment resulted in a 51.3% yield, 10.8% water content, 5% ash content, 775.41 equivalent weight, and 6.49 methoxyl content. The intense FTIR spectrum in the ―CO―CH3 and ―COOH groups showed the same result as the standardised pectin.